HEART RATE VARIABILITY IN STRESS-INDUCED HYPERTENSION - I. V. Osipova; O. N. Antropova; K. I. Shakhmatova; K. G. Golovina; A. G. Zaltsman (Российский кардиологический журнал, 2009)
The study was aimed at identifying the features of heart rate variability (HRV) in patients with workplace arterial hypertension (WPAH). The study included 329 men with AH, divided into two groups, according to their blood pressure monitoring results: Group I – 197 WPAH individuals, and Group II – 132 patients with essential AH (EAH). All participants underwent the five-minute HRV recording, with the analysis of temporal, spectral and histogram parameters. It was demonstrated that HRV parameters were influenced by patient age, AH stage and duration. In people aged over 40 years, WPAH was associated with increased sympathetic tone, reduced adaptation potential of cardiovascular system, and decreased humoral effects on HR, comparing to EAH. Additionally, WPAH patients with Stage I, comparing to their peers with EAH, demonstrated increased sympathetic tone, while Stage II was linked to reduced cardiovascular adaptation potential and humoral influences.